A Woman in Her Forties with Six Months of Worsening Dyspnea - Kumar, Dilpat; Nguyen, Minh HN; Kenth, Simran S; Warsha, FNU (International Journal of Medical and Health Sciences Research, 2021)
Uterine leiomyosarcoma (ULMS) is a rare cancer that originates from the smooth muscle of the uterine wall. ULMS is aggressive with a high rate of recurrence and mortality. Although the majority of ULMS are initially diagnosed within the uterus, they possess a high metastatic potential. Two thirds of metastatic ULMS sites involve the lung. However, the clinical presentations of such metastases are surprisingly not well described. In this case, we describe a case of a woman in her forties who presented with 6 months of worsening dyspnea and chronic cough. Her pulmonary function test demonstrated severe restrictive lung disease. Computed tomography (CT) of the chest was done which showed multiple pulmonary nodules. CT abdomen and pelvis identified multiple uterine masses with largest being 17 cm. Biopsy of uterine masses confirmed the diagnosis of UMLS. Her restrictive lung disease was diagnosed to be secondary to UMLS, as patient had no other identifiable risk factors.